If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + ycosx) * dx + senxdy = 0 Reorder the terms: (cosxy + x) * dx + senxdy = 0 Reorder the terms for easier multiplication: dx(cosxy + x) + senxdy = 0 (cosxy * dx + x * dx) + senxdy = 0 (cdosx2y + dx2) + senxdy = 0 Reorder the terms: cdosx2y + densxy + dx2 = 0 Solving cdosx2y + densxy + dx2 = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1densxy' to each side of the equation. cdosx2y + densxy + -1densxy + dx2 = 0 + -1densxy Combine like terms: densxy + -1densxy = 0 cdosx2y + 0 + dx2 = 0 + -1densxy cdosx2y + dx2 = 0 + -1densxy Remove the zero: cdosx2y + dx2 = -1densxy Add '-1dx2' to each side of the equation. cdosx2y + dx2 + -1dx2 = -1densxy + -1dx2 Combine like terms: dx2 + -1dx2 = 0 cdosx2y + 0 = -1densxy + -1dx2 cdosx2y = -1densxy + -1dx2 Divide each side by 'dosx2y'. c = -1eno-1x-1 + -1o-1s-1y-1 Simplifying c = -1eno-1x-1 + -1o-1s-1y-1
| 6*x^2=96 | | f(x)=6x-8x^3 | | 5.5a/2 | | (x+y)4=92 | | 18*x^2=96 | | (3x-4)/4=(4x-2)/6 | | 2x+x=28 | | -3x+15=6x | | X+2X=85 | | 86.20= | | u=(x+1)(1-y) | | 2+7x=9+3x+2 | | y=0.2x+6.2 | | sinx/cosx=y | | ydx=dy | | 2x*-1x-1*-1=0 | | 2x*-1*x*-1=0 | | 98=x*8+2 | | 3x+2=23-4x | | 130+40+x=360 | | 3x-1/7=5 | | px+8=3 | | 2x=58m | | f(6)=13x+1 | | 12x=9-6 | | 3cos3(3pi/2) | | sen(3x)-sen(5x)=0 | | 8x+6x=29 | | 21x^2+150x=1000 | | 8x+11=63 | | -4p-7=-5+8p | | 6/5х=3/5 |